2016
DOI: 10.5812/ircmj.34609
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Dynamics of HIV-I Subtype B and Circulating Recombinant Form 01_AE Clades in Iran: A Phylogeographic Approach

Abstract: Background: The origins and spatio-temporal dynamics of the HIV-1 subtype B and CRF01_AE clades are largely unknown in Iran. Objectives: This study investigates the origins and spatio-temporal dynamics of HIV-1 subtype B and CRF01_AE clades in Iran using the most recent phylogeographic methods. Methods: This Bayesian phylogeographic study examined HIV-1 sequence data available in the Los Alamos HIV databases. For the purposes of this study, we retrieved all the eligible time-stamped and geo-referenced HIV-1 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…However, in another study conducted by Eybpoosh, et al (2016), on all HIV-1 subtype B strains available from Iran revealed that multiple parallel subtype B epidemics existed in Iran with independent origins. They noted that the subtype B epidemic observed among heterosexuals, has an independent evolutionary history from the epidemic observed among hemophiliac patients and is probably imported to Iran from USA, Germany, and Hong Kong, but not from France ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study conducted by Eybpoosh, et al (2016), on all HIV-1 subtype B strains available from Iran revealed that multiple parallel subtype B epidemics existed in Iran with independent origins. They noted that the subtype B epidemic observed among heterosexuals, has an independent evolutionary history from the epidemic observed among hemophiliac patients and is probably imported to Iran from USA, Germany, and Hong Kong, but not from France ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…To identify any export events of CRF01_AE strains related to Chinese major transmission clusters, we quantified the genetic divergence time in terms of the estimated time to the most recent common ancestor (tMRCA) using a Bayesian MCMC-based approach and also estimated the location of ancestor at the node of the tree. Many sequences (1172 from China and 226 from Vietnam) were identified to be associated with viral transmission in China through above phylogenetic analysis, and to reduce the computational burden in Bayesian running for spatialtemporal analysis, a sub-sampling procedure was performed that only one representative sequence was selected among high similarity clustered sequences (genetic distance < 2%), using the online web server of CD-HIT-EST program (Huang et al, 2010;Eybpoosh et al, 2017). As a result, totally 328 sequences (186 from Mainland China, 56 from Vietnam, 88 from other countries/regions) and 42 references were used for the FIGURE 2 | Phylogenetic analysis of global CRF01_AE strains outside Mainland China together with five major Chinese clusters.…”
Section: The Spatial-temporal Scale Of Hiv-1 Crf01-ae Strains Associamentioning
confidence: 99%